2011
DOI: 10.29333/ejgm/82696
|View full text |Cite
|
Sign up to set email alerts
|

Anticarcinogenic Activity of Allylmercaptocaptopril Against Aflatoxin-B1 Induced Liver Carcinoma in Rats

Abstract: Aim

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…HEX levels are important in determining the glycolytic capacity of cancer cells. [ 20 21 ] Increased activities of HEX and PGI during development of tumor cells observed in the present study are in agreement with the finding of earlier study,[ 22 ] wherein the increased activities of glycolytic enzymes have been found to correlate with the degree of malignance in tumor tissues. High levels of HEX reported in Novikoff and Zajdela hepatomas and aflatoxin-B1 induced liver carcinoma[ 22 23 24 ] signify the functional importance of HEX in tumor cells to utilize excess glucose for the production of ATP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…HEX levels are important in determining the glycolytic capacity of cancer cells. [ 20 21 ] Increased activities of HEX and PGI during development of tumor cells observed in the present study are in agreement with the finding of earlier study,[ 22 ] wherein the increased activities of glycolytic enzymes have been found to correlate with the degree of malignance in tumor tissues. High levels of HEX reported in Novikoff and Zajdela hepatomas and aflatoxin-B1 induced liver carcinoma[ 22 23 24 ] signify the functional importance of HEX in tumor cells to utilize excess glucose for the production of ATP.…”
Section: Discussionsupporting
confidence: 93%
“…[ 21 ] Decreased rate of glucose-6-phosphatase mediated dephosphorylation is also reported in malignant cells. [ 31 ] Decreased activity of fructose-1,6-bisphosphatase, the key regulatory enzyme for the synthesis of glucose-6-phosphate from pyruvic acid observed in liver of Group III rats is supported by the earlier report,[ 22 ] which reported that in aflatoxin-B1 induced liver carcinoma, there appears to be a decreased fructose-1,6-bisphosphatase in the tumor and consequently a block in the pathway, leading to the synthesis of glucose-6-phosphate from pyruvate.…”
Section: Discussionmentioning
confidence: 56%
“…Our data were supported by other previous findings; Frederiks et al (2008) demonstrated that chemically induced HCC in rats was characterized by increased G6PDH activity. Sharma, Lakshmi, Chitra, Lakshmi, and Pharm (2011) reported an increased aldolase activity in rats with induced HCC. Schlichtholz et al (2005) reported a significant increase in citrate synthase activity in human pancreatic cancer.…”
Section: Discussionmentioning
confidence: 98%